2020
DOI: 10.4236/psych.2020.119088
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of the Tacit Knowledge Inventory for High School Teachers in a Greek Context

Abstract: This study presents the factor structure underlying Tacit Knowledge Inventory for High School Teachers (TKI-HS) which constitutes an informative measure for the assessment of experienced-based tacit knowledge of Greek secondary school teachers, as well as the effect of the teaching experience factor on teachers' preferred strategies for their workplace interactions. The aim of this study was to provide an insight into the factor structure underlying this instrument in a Greek context, as the structure of its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Type of questions : Year Both the assessment indicators and statistical information stand alone do not have any representations and it is meaningless without others being analysed altogether [8]. Furthermore, in order to have an effective and efficient online learning outcome for the learner, the assessor requires to design and develop the curriculum, learning materials and Q&A using a hybrid integrated model [9]. The curriculum needs to be an all rounded learning blueprint, where learner can improve their understanding in a progressive manner and user-friendly approach.…”
Section: Methodsmentioning
confidence: 99%
“…Type of questions : Year Both the assessment indicators and statistical information stand alone do not have any representations and it is meaningless without others being analysed altogether [8]. Furthermore, in order to have an effective and efficient online learning outcome for the learner, the assessor requires to design and develop the curriculum, learning materials and Q&A using a hybrid integrated model [9]. The curriculum needs to be an all rounded learning blueprint, where learner can improve their understanding in a progressive manner and user-friendly approach.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, tacit knowledge is related to goal achievement, an action that has great personal significance for each person individually. The higher a goal is, the more directly the achievement of that specific goal rests on knowledge and the more useful knowledge is ( Foutsitzi et al 2020 ). Furthermore, tacit knowledge acquisition is not achieved by environmental support.…”
Section: Introductionmentioning
confidence: 99%
“…The most decisive factor in obtaining it is the way in which a person manages the experiences they gain in their professional environment. The development of expertise, regardless of the professional field, results from a process in which a maximum and conscious effort is made, which favors the accumulation of tacit knowledge that can be easily stored effectively and used to recognize analogies in the conditions that arise, enabling fast and effective decision making ( Sternberg et al 2001 ; Foutsitzi et al 2020 ; Stemler et al 2006 ; Scully et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, measures of tacit knowledge and practical intelligence may become particularly relevant for the selection and evaluation of teachers. In the past, these tests have typically been conducted using a text-based situational judgment test (Elliot et al, 2011;Foutsitzi, Papantoniou, Karagiannopoulou, Zaragas, & Moraitou, 2020;Stemler et al, 2018), but recent research has shown promise for animating these situational judgment tests to increase the validity of the measurement (Karakolidis, O'Leary, & Scully, 2021), thus providing an even more promising tool for the selection and evaluation of teachers.…”
Section: Highlightmentioning
confidence: 99%
“…However, they don't yet hold the relevant experiences that would allow them to identify and potentially avoid the less effective solutions to the same challenging situations. Therefore, measures of tacit knowledge, as discussed by Foutsitzi et al (2020), can be used to identify the difficulties or weaknesses of teachers in how they respond to unfamiliar situations and then target those weaknesses in teacher education or professional development programs. This is exemplified by Elliott and Stemler (2008) as they discuss how some of the components of teaching that are traditionally tacit in nature can be made explicit through training.…”
Section: Highlightmentioning
confidence: 99%